Kemampuan Berpikir Kreatif Siswa Sekolah Dasar Dalam Pembelajaran IPA Menggunakan Model Pembelajaran RADEC - Wahyu Sopandi; Atep Sujana; Lungguh Puri Pramswari; Sabila Idzni Suryana (Postgraduate, University of Mataram, 2021)
The purpose of this research is to know the creative thinking ability of elementary school students through the RADEC learning model. This research was conducted using a descriptive qualitative method involving 38 students in fifth grade in an elementary school in Sumedang Regency, West Java. This research was conducted in science learning at air topic. Data collection was carried out using instruments in the form of tests, questionnaires, and observation guidelines. The research data is processed by determining the percentage value of the student's answers then calculating the average value based on aspects of the creative thinking indicator. The results showed that the students' initial creative thinking ability was in the medium category. However, after the use of the RADEC learning model, students' creative thinking abilities increased and entered the high category with the difference in percentage values ​​through questionnaires and tests accompanied by observations, respectively, of 25% & 16% for the fluency aspect, 12.50% ​​& 18.80% for the flexibility aspect, 27.50% & 10.20% for the authenticity aspect, and 24.90% & 17.50% for the detail aspect. Based on the results of the questionnaire and observations, an increase in high thinking skills can occur because the phases in the RADEC learning model require students to be more active in expressing opinions, refuting, asking questions, finding solutions to a problem, and creating something new